Insight into the wear particles of PEEK and CFRPEEK against UHMWPE for artificial cervical disc application: Morphology and immunoreaction. (April 2020) - Song, Jian; Chen, Fangfei; Liu, Yuhong; Wang, Song; He, Xiang; Liao, Zhenhua; Mu, Xiaohong; Yang, Mengying; Liu, Weiqiang; Peng, Zhongxiao
Abstract: Artificial cervical disc is a key device for artificial cervical disc replacement (ACDR). In our previous study, we developed PEEK-on-UHMWPE and CFRPEEK-on-UHMWPE tribo-parings for artificial cervical disc application. To further evaluate the biotribological properties and potential inflammation responses of their by-products, the size distribution and morphological characteristics of collected post-test wear particles as well as the biological response of aggregated particles were studied. Our results indicated that the majority of these wear particles were in a size range of 0.05–25 μm and the possibility of immunoreaction was small. Thus, we provide further evidence from the wear particles' point of view to suggest that CFRPEEK-on-UHMWPE can be considered as the potential paring for artificial cervical disc application. Graphical abstract: Image 1 Highlights: The wear particles were in a size range of 0.05–25 μm. The possibility of immunoreaction induced by the particles was small. CFRPEEK-on-UHMWPE can be considered as a paring for artificial cervical disc.